Investment In Spreading Criminal Law for Rural Indigenous Communities - Gultom, Sarles; Saragih, Sepriandison (Future Science / FSH-PH Publications, 2022)
This study discusses the understanding and dissemination of legal awareness in society, especially criminal law in social life. The author believes that early prevention efforts to minimize unlawful acts are indispensable in every context of legal socialization events. By socializing the law, all citizens aim to create a just and prosperous, safe and prosperous society free from crime, security disturbances, and anarchy. The better the socialization of criminal law, the easier it will be for the community to be invited to achieve independence in order to increase legal awareness. This socialization is the responsibility of all parties, especially the academic community and state apparatus, to guide citizens, especially indigenous peoples in remote parts of the country, to produce peaceful, capable, disciplined, responsible, and courageous citizens who are honest in life. This study also hopes that narrative narratives and academic thoughts on criminal law in indigenous peoples become ceremonial events. Law must be a life-giving culture, especially for indigenous peoples, to be a good example for other communities. Condor has been studied in several legal publications and other sources we have reviewed to answer the most valid research questions. This is also to ensure the data review process runs smoothly and responsibly.